Migrant Diplomacies: Rethinking the Civic-Bi-Nationality in North America - Alejo, Antonio (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2020)
Given the challenges of contemporary human mobility, it is necessary to think about the ability of migrants to defend their rights. Our starting point is that it is necessary to go beyond the state-centric perspectives to analyze migrant activisms when in the name of sovereignty and national interest, migrants face negative environments that inhibit their free movement. With an interdisciplinary dialogue, between the sociology of collective action and diplomatic theory, we propose the notion of migrant diplomacies as a way to address migrant activisms in North America, based on binational activisms in the face of deportation and return processes. In this analysis we identify that binational activisms as pos-national civic project that looks to act here and there, simultaneously. With a multi-case study approach, we use two binational organizations in North America to demonstrate how these types of migrant diplomacies operate.
Keywords: migrant diplomacies; civic bi-nationality; North America; deportees; returnees